COST OF GOVERNANCE AND ECONOMIC DEVELOPMENT: AN EMPIRICAL ANALYSIS OF PRESIDENCY, NATIONAL ASSEMBLY AND JUDICIARY EXPENDITURE IN NIGERIA (Journal of Business Management and Accounting, 2023)
It is expected that increase in cost of governance by government should bring about a commensurate increase in the level of economic development of a country, but this seems not to be the case in Nigeria. It is on this premise that the study investigated how cost of governance is related to economic development in Nigeria. The focus of the study is on how presidency expenditure, national assembly expenditure and federal judiciary expenditure are related to economic development (unemployment rate, gross domestic product per capita and inflation rate). The study used time series methodology and it covered a period of five years (2016-2020). The data for the study were obtained from Central bank of Nigeria Website and analyzed using inferential statistics. Findings from regression analysis showed that presidency expenditure and national assembly expenditure have negligible and insignificant relationship with unemployment rate. It was also found that judiciary expenditure is insignificantly and negatively related to unemployment rate. Moreover, results revealed that presidency expenditure and national assembly expenditure are negatively related to gross domestic product per capital, whereas there is a positive relationship between judiciary expenditure and gross domestics product per capital, although these relationships are significant. Besides, results showed that presidency expenditure is positively and significantly related to inflation rate. It was also found that there is insignificant positive relationship between national assembly expenditure and inflation rate. However, the study found that the relationship between judiciary expenditure and inflation rate is positive and significant. The study concludes that increase in presidency expenditure and national assembly expenditure tends to worsen economic development, while increase in judiciary expenditure may improve economic development in Nigeria. Therefore, it is recommended that government should reduce budget allocations to presidency and national assembly, while there should be increase in budget allocation to the judiciary to improve economic development.